Very Early-Onset Inflammatory Manifestations of X-Linked Chronic Granulomatous Disease - Labrosse, Roxane; Abou-Diab, Jane; Blincoe, Annaliesse; Cros, Guilhem; Luu, Thuy Mai; Deslandres, Colette; Dirks, Martha; Fazilleau, Laura; Ovetchkine, Philippe; Teira, Pierre; LeDeist, Françoise; Fernandez, Isabel; et al. (Frontiers in Immunology, 2017)
Chronic granulomatous disease (CGD) is a rare primary immune deficiency caused by mutations in genes coding for components of the NADPH oxidase, characterized by severe and recurrent bacterial and fungal infections, together with inflammatory complications. Dysregulation of inflammatory responses are often present in this disease and may lead to granulomatous lesions, most often affecting the gastrointestinal and urinary tracts. Treatment of inflammatory complications usually includes corticosteroids, whereas antimicrobial prophylaxis is used for infection prevention. Curative treatment of both infectious susceptibility and inflammatory disease can be achieved by haematopoietic stem cell transplantation. We report herein three patients with the same mutation of the CYBB gene who presented with very early-onset and severe gastrointestinal (GI) manifestations of X-linked CGD. The most severely affected patient had evidence of antenatal inflammatory involvement of the GI and urinary tracts. Extreme hyperleukocytosis with eosinophilia and high inflammatory markers were observed in all 3 patients. A Mycobacterium avium lung infection and an unidentified fungal lung infection occurred in two patients both during their first year of life, which is indicative of the severity of the disease. Two patients underwent bone marrow transplantation (BMT) and recovered fully from their initial symptoms. To our knowledge, these are the first reports of patients with such an early-onset and severe inflammatory manifestations of CGD.